Running a Contest to Encourage Timely Monograph Ordering - Cramer, Carol Joyner (My University, 2012)
An age-old problem: Whatever deadline you set for placing monograph orders, you receive a big burst of orders at the last minute. Acquisitions staff beg for book orders one month and get flooded with orders the next. Librarians at Wake Forest University tried to mitigate this problem by running at contest: spend 65% of your target by an early deadline, and your fund wins a share of a cash prize. The presenter will discuss how the contest idea proved an effective incentive for selectors and how it served to make acquisitions work more steadily.
Keywords: collection management; monographs; incentives